Validation of a brief step-test protocol for estimation of peak oxygen uptake. - Beutner, F.; Ubrich, R.; Zachariae, S.; Engel, C.; Sandri, M.; Teren, A.; Gielen, S. (Eur J Prev Cardiol, 2015)
BACKGROUND: Physical exercise capacity has been shown to predict cardiovascular disease incidence and is increasingly measured in epidemiological studies. However, direct measurement of peak oxygen uptake is too time consuming in large-scale studies. We therefore investigated whether a brief 3-minute step-test protocol can be used to estimate peak oxygen uptake in these settings. DESIGN AND METHODS: A group of 97 subjects performed the YMCA step test and a maximal treadmill test with continuous measurement of oxygen uptake. Correlation and linear regression analyses were used to identify VO2peak predictors obtained from the step test and to develop models for VO2peak estimation. RESULTS: The YMCA model, including the 1-minute heart beat count, predicted VO2peak with R = 0.83. A novel simplified model based on the heart rate at 45 s of recovery performed comparable (R = 0.83). However, models based on heart rate measures were only valid in subjects who completed the test according to protocol, but not in subjects who terminated prematurely. For the applicability in subjects with low exercise capacity, a new model including gas exchange analysis enabled prediction of VO2peak (R = 0.89). All models were validated in an independent sample (r = 0.86-0.91). Exercise time of the step test was less than one-hird of standard ergospirometry (treadmill test: 654 +/- 151 s, step test: 180 s, p < 0.001). CONCLUSION: In large-scale epidemiological studies with limited time slots for exercise testing and significant proportions of subjects with low exercise capacity a modified version of the YMCA step test may be used to predict VO2peak.
Keywords: Adult; Aged; Breath Tests; Electrocardiography; *Exercise; Exercise Test/*methods; Exercise Tolerance; Female; Heart Rate; Humans; Linear Models; Male; Middle Aged; Models, Biological; *Muscle Contraction; Muscle, Skeletal/*metabolism; *Oxygen Consumption; Predictive Value of Tests; Reproducibility of Results; Time Factors; Young Adult